The correlations between periodontal disease in the woman with pregnancy and low birth weight infant: a systematic review: Hubungan antara penyakit periodontal pada wanita hamil dengan berat bayi lahir rendah: kajian sistematik - Ira Farwiany Syafar; Hasanuddin Tahir; Sri Oktawati (Makassar Dental Journal, 2019)
Objective: To study the correlations of periodontal disease in the woman with pregnancy and low birth weigth infant (LBWI). Methods: Pubmed and Wiley online searches were conducted to identify articles published in dental journals from January 2013 to November 2018 focusing on pregnancy women and LBWI and its correlations with periodontal disease.Manual searchesof published full-text articles and related reviews were performed afterwards. Result: The initial database search produced 44 articles. A total 6 studies were selected for inclusion, with total 995 pregnancy women as subjects. All of the studies showed the associations of plaque index(PI),gingivalindex(GI),probingdepth(PD),bleedingonprobing(BOP),clinicalattachmentloss(CAL), gestational age (GA) and birth weight.Conclusion:Periodontaldiseaseinthepregnancy women is one risk factor for adverse pregnancy outcomes such as infant low birth weight.